ANALISIS PERUMUSAN KEBIJAKAN DAN POTENSI PAJAK MINERAL BUKAN LOGAM DAN BATUAN DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH (Studi Pada Kabupaten Blora) - Alfiyah, Ummahatun (Jurnal Mahasiswa Perpajakan, 2014)
Many mining issues of nonmetallic mineral and rocks that occur in Blora Regency, as well as the mining sector has not been able to contribute maximally to the original income of Blora from tax sector. One of the many causes of illegal mining and not maximum contribution from the tax sector is the absence of mining regulations. How does the process of policy formulation mining and whether the formulation process of the local government entitles miners, other interested parties and a neutral party to participate. The results of the study showed that the government of Blora regency provide an opportunity to the parties concerned and netral to show their aspirations appropriate with the formulation of a model of democratic. This model requires that every person who has the right to be included as much as possible.The results of this study also indicate that the potential tax Blora owned quite large. Based on the calculation, based on volume, based price, and the tax rate, then in 2012 the tax potential from illegal mining tax is Rp 1,192,225,000. Keywords : Policy Formulation, Tax Non Metallic Minerals and Rocks, Government